ANALISIS PROFITABILITAS USAHA PADA DERMAGA UMUM DI MUARA BADAK - Haidir, Muhammad Kurnia; Saher, Sayid; Hendra (I-Con Media, 2023)
The birth of several small businesses as well as large businesses in the Muara Badak District, especially in the field of transportation services, has provided evidence that economic development in the Muara Badak District is increasingly advanced. The evidence can be seen with the variety of types of businesses that began to develop, one of which is the Public Docksin Muara Badak, which is one of the crossing businesses with a tariff of Rp. 2,000 per person at Pangempang Road Rt 05. No 28. Muara Badak Distric. The main objective of this study is to find out and assess the financial performance of Orange Pier which is reviewed using profitability ratios in 2017 and 2018. The analytical tool used in this study is a financial ratio analysis tool as a basis for measuring profitability ratios for analysis results. Profit Margin is the company's ability to generate profits compared to sales achieved. From the results of the calculation of profit margins in 2017 showed 57.37% and 2018 showed 62.88% of the difference in increase achieved 5.51% from 2017. Turnover of Operating assets shows the company's ability with all the capital in it to generate profits. This ratio is calculated by comparing earnings before interest and taxes with total assets. This ratio is used to measure the ability to generate net income based on the level of assets. From the results of calculations in 2017 showed 71.02% and 2018 showed 75.30% difference experienced an increase in 2018 was 4.28%. Return On Investment (ROI) is used to determine the effectiveness of the company in utilizing funds from the company. From the calculation results obtained ROI increased in 2018 by 6.60% from the results of 2017 showing 40.74 and 2018 showing 47.34%.